2012
DOI: 10.1371/journal.pone.0033097
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Indirect Fluorescent Antibody Assays Compared to Rapid Influenza Diagnostic Tests for the Detection of Pandemic Influenza A (H1N1) pdm09

Abstract: Performance of indirect fluorescent antibody (IFA) assays and rapid influenza diagnostic tests (RIDT) during the 2009 H1N1 pandemic was evaluated, along with the relative effects of age and illness severity on test accuracy. Clinicians and laboratories submitted specimens on patients with respiratory illness to public health from April to mid October 2009 for polymerase chain reaction (PCR) testing as part of pandemic H1N1 surveillance efforts in Orange County, CA; IFA and RIDT were performed in clinical setti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 19 publications
2
9
0
Order By: Relevance
“…That is comparable to previously published studies for rapid tests, including the Directigen Flu A+B. 5,14,15 The overall sensitivity of Directigen Flu A+B in the present study using combined nose and throat swabs is 48.5% for infl uenza A and 13.3% for infl uenza B which is lower than what has been found in other studies. In general, rapid tests show lower sensitivity than the sensitivity of PCR.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…That is comparable to previously published studies for rapid tests, including the Directigen Flu A+B. 5,14,15 The overall sensitivity of Directigen Flu A+B in the present study using combined nose and throat swabs is 48.5% for infl uenza A and 13.3% for infl uenza B which is lower than what has been found in other studies. In general, rapid tests show lower sensitivity than the sensitivity of PCR.…”
Section: Discussionsupporting
confidence: 87%
“…Many studies have demonstrated that early initiation of oral oseltamivir therapy increased its therapeutic effects reducing the duration of the symptoms, severity of the illness, incidence of secondary complications, and duration of the hospitalization. [3][4][5] Infl uenza can be diffi cult to diagnose based on clinical signs and symptoms alone because infl uenza illness can be similar to illness caused by other infectious agents including parainfl uenza viruses, adenovirus, respiratory syncytial virus and Legionella spp. 1,2,6 Timely diagnosis and treatment of patients with infl uenza is the reason why physicians need rapid infl uenza diagnostic tests with high sensitivity requiring no complex lab equipment and being able to be performed and interpreted easily within 15 minutes.…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that the sensitivity of the rapid influenza diagnostic test (RIDT) for the detection of influenza A (H1N1) pdm09 varied between 18% and 69%. The sensitivity results for DFA were also different and ranged from 47% to 93% [3436]. In the present study, a great similarity was observed between the results of the conventional methods (culture and DFA), our designed assay and those of the WHO.…”
Section: Discussionsupporting
confidence: 59%
“…Complicating the assessment of the usefulness of these assays is that the performance seems to vary between influenza strains and, unfortunately, during the H1N1 09 pandemic they were less than optimal. [43][44][45][46][47] A recent metaanalysis of 159 published studies of rapid influenza tests found the pooled sensitivity, sensitivity, specificity, and positive and negative predictive values to be 62%, 98%, 34%, and 38%, respectively. 47 Not surprisingly, given these data, there is little evidence that rapid influenza tests are currently used by clinicians to alter patient management.…”
Section: Influenzamentioning
confidence: 99%